Community Trust in Village Financial: The Role of External Pressure and Corruption Perception - Susilowati, Nurdian; Elisabet, Camelia Yunika; Abdullah, Muhammad Syukri; Paranti, Lesa; Amidi, Amidi (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2023)
Community trust in village financial management has an important role. The fantastic value of village funds encourages the community to participate in its management. The facts show that the amount of village funds has triggered the village apparatus to act corruptly, so in 2018, many village heads and village apparatus were in jail. This study aims to determine the effect of external pressure, transparency, accountability, and corruption perception on public trust. This study used a survey method with hypothesis testing, and it was conducted in the Tegal Regency. The sampling technique used was cluster sampling and obtained 103 respondents. This study used questionnaires to collect the data. It also analyzes the data using descriptive and path analysis (structural equation modeling) with WarpPLS. The results show that external pressure directly influences the transparency and accountability of village governments. Transparency has a direct effect on accountability. Transparency and accountability have a positive influence on community trust. Meanwhile, the corruption perception has a negative influence that weakens public trust. Perceptions of corruption also have a mediating role in the indirect relationship between transparency and public trust. However, this study only examines from the perspective of village officials. Further research should explore the transparency and accountability of village governments from the community point of view.